Gender-dependent Differences in the Relationship between Diabetes Mellitus and Ambient Air Pollution among Adults in South Korean Cities - Dongwook SOHN; Hyunjin OH (Tehran University of Medical Sciences, 2017)
Background: Air pollution has been a serious public health threat worldwide. It has been linked to pulmonary and cardiovascular diseases but is also believed to contribute to air-pollution-mediated cardiometabolic disease such as diabetes. We investigated the relationship between type 2 diabetes mellitus (DM2) and air pollution in densely developed urban settings in South Korea, using national epidemiologic data. Methods: The analysis focused on examining gender-related differences in the relationship between DM 2 and air pollutants, specifically particulate matter ≤ 10μm (PM10) and sulfur dioxide (SO2). To assess the relationship between DM and exposure to PM10 and SO2, multivariate logistic regression models were developed using the 2012 Korea Community Health Survey data and the ambient air pollution data in South Korean cities at both Gu- and Si levels. Results: The commonly encountered levels of PM10 and SO2 may be associated with DM 2 prevalence in South Korea but it appears there may be gender differences. In particular, exposure to either PM10 or SO2 was significantly related to the prevalence of DM 2 among women but not among men. Conclusion: These findings provide new evidence of an association between air pollution and the risk of diabetes in urbanized areas of South Korea.